2016
DOI: 10.1080/09638288.2016.1196396
|View full text |Cite
|
Sign up to set email alerts
|

The association between muscle strength and activity limitations in patients with the hypermobility type of Ehlers–Danlos syndrome: the impact of proprioception

Abstract: Purpose: The patients diagnosed with Ehlers-Danlos Syndrome Hypermobility Type (EDS-HT) are characterized by pain, proprioceptive inacuity, muscle weakness, potentially leading to activity limitations. In EDS-HT, a direct relationship between muscle strength, proprioception and activity limitations has never been studied. The objective of the study was to establish the association between muscle strength and activity limitations and the impact of proprioception on this association in EDS-HT patients. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 45 publications
(73 reference statements)
2
68
1
1
Order By: Relevance
“…The 6MWT distance was likely enhanced by an improvement of the aerobic pathway. This improvement of physical functional capacity can also be explained by the content of the program in which muscle strengthening and proprioception are important elements and have been suggested to be related to activity limitations (Scheper et al, 2017). We found a significant mean improvement for the 6MWT distance higher than the MCID.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The 6MWT distance was likely enhanced by an improvement of the aerobic pathway. This improvement of physical functional capacity can also be explained by the content of the program in which muscle strengthening and proprioception are important elements and have been suggested to be related to activity limitations (Scheper et al, 2017). We found a significant mean improvement for the 6MWT distance higher than the MCID.…”
Section: Discussionsupporting
confidence: 53%
“…All assessments were conducted on the baseline (t0), at the end of the program (t9), and 6 weeks after the end (t15). These assessments have been already used in hEDS in the literature (e.g., Scheper et al (2017);Celletti et al (2013)) and all the questionnaires have been validated in French.…”
Section: Methodsmentioning
confidence: 99%
“…Impaired proprioceptive acuity is thought to influence muscle strength. Therefore, improving muscle strength on the basis of proprioceptive impairment may be more important for reducing activity limitations than just improving muscle strength 80. Chiari 1 malformation type 1 was found in 4.7% of EDS-HT patients19 and may be associated with cranio-cervical instability and/or the tethered cord syndrome.…”
Section: General Characteristics and Manifestationsmentioning
confidence: 99%
“…Also, some evidence was found that muscle strength and functional performance of the lower extremity is reduced in women with hypermobile Ehlers-Danlos syndrome [15]. The same group found in a previous study that patients with hypermobile Ehlers-Danlos syndrome demonstrated a significant impairment in knee joint reposition sense and a lower level of sports and physical activity than controls [16]. A systematic review and metaanalysis showed that lower limb proprioception is reduced in people with GJH [17].…”
Section: Introductionmentioning
confidence: 75%
“…The second study was done with adults suffering from Ehlers-Danlos syndrome type III (hypermobility type). In this study the hypermobile patients showed a lower activity level in sports than controls [16]. Finally Schmidt et al [23] investigated how people with JHS make decisions about physical activity.…”
Section: Discussionmentioning
confidence: 99%